Cover Picture: The Pivotal Role of Catalysis in France: Selected Examples of Recent Advances and Future Prospects. (ChemCatChem 12/2017). Issue 12 (22nd June 2017) - Olivier‐Bourbigou, Hélène; Chizallet, Céline; Dumeignil, Franck; Fongarland, Pascal; Geantet, Christophe; Granger, Pascal; Launay, Franck; Löfberg, Axel; Massiani, Pascale; Maugé, Françoise; Ouali, Armelle; Roger, Anne‐Cécile; et al.
Abstract : The Front Cover shows the potential of catalysis in France.In their Review, H. Olivier‐Bourbigou et al. summarize the most significant breakthroughs reported in France over the last ten years in the field of heterogeneous catalysis. The Review focuses on the development of catalytic systems for specific applications, such as petrochemistry, biomass transformation, environmental applications and CO2 for energy. The significant cross‐disciplinary approaches, essential to understand and optimize catalytic processes, are also described. More information can be found in the Review by H. Olivier‐Bourbigou et al. onpage 2029 in Issue 12, 2017 (DOI:10.1002/cctc.201700426 ).